Peritoneal dialysis as the first dialysis treatment option initially unplanned - Mendes, Marcela Lara [UNESP]; Alves, Camila Albuquerque [UNESP]; Bucuvic, Edwa Maria [UNESP]; Dias, Dayana Bitencourt [UNESP]; Ponce, Daniela [UNESP] (FapUNIFESP (SciELO), 2017)
Most patients with stage 5 CKD start RRT of unplanned manner. Unplanned dialysis, also known as urgent start, may be defined as hemodialysis (HD) started without permanent vascular access, i.e., using a central venous catheter (CVC), or as peritoneal dialysis (PD) started within seven days after implantation of the catheter, without family training. Although few studies have evaluated the PD as an immediate treatment option for patients starting urgent RRT, theirs results suggest that it is a feasible and safe alternative, with infectious complications and survival similar to patients treated with unplanned HD. Given the importance of the social role of urgent start of dialysis and the lack of studies on the subject, this narrative review aims to analyze and synthesize knowledge in published articles, preferably, from last five years in order to unify information and facilitate future studies.